A New Class of Biocompatible Tricalcium Phosphate/ Polypropylene Carbonate/ Polylactic Acid Nanocomposites with Controlled Flexibility and Biodegradability - Yang, Ta-I; Lin, Po-Liang; Chang, Guang-Wei; Tseng, Yu-Chen; Yu, Zhe-Yang; Yang, Charng-Bin; Dong, Guo-Chung; Fang, Hsu-Wei (Current Nanoscience, 2014)
The goal of this research is to improve the mechanical and biological properties of widely used polylactic acid (PLA) in order to enhance the mechanical processability and bioactivity performance of the PLA-based medical implants. A polypropylene carbonate (PPC) polymer was utilized to control the bending strength of the PLA composites, leading to elastic PLA composites without any nontoxicity to osteoblast-like cells. Furthermore, a bioceramic material, tricalcium phosphate (β-TCP), was also introduced to further finetune the mechanical properties of the PLA composites. Experimental data revealed that the resulting elastic β-TCP/PPC/PLA nanocomposites exhibited elongation at break (%) of 1100% with tensile strength close to 1 MPa. The method developed in this study provides a simple strategy for fabricating biodegradable PLA based-materials with desired mechanical processability and malleability at room temperature.
Keywords: polypropylene carbonate